“I Am from the Ghetto, I Am Black, I Live in the Slum and They Think: Why Bother with Her?” – Racism in Seeking Help Experiences for Domestic Violence in Brazil - Pereira, Stephanie (Journal of interpersonal violence, 2025)
Despite the majority of Brazilians identifying as black, racial disparities are significant. Black women encounter disproportionate difficulties, with greater rates of homicide, unemployment, and poverty. After the Maria da Penha Law (2006), which is regarded as one of the most comprehensive laws to address domestic violence, there has been a notable increase in femicide among black women and a decrease in cases among white women. This paper aims to analyze the differences between white and black survivors of domestic violence in terms of the access and support they received from the violence against women multi agency network in the city of São Paulo, Brazil. To this end, in-depth interviews (IDI) were conducted with nine white and nine black women who were seeking help in the justice system in June of 2018. The IDI were analyzed under critical path and structural racism theories, in order to understand how inequality markers such as race might affect the institutional response to the survivor’s help seeking. The results indicated that black women received less information and support while seeking institutional help, as they faced more obstacles compared to white women. Among the interviewees critical paths, the access to the services was denied by providers 13 times for black women in contrast with 1 access denial for white women—also considering cases that discontinued the needed assistance due to institutional violence. The observed obstacles lived by black women in the multiagency network not only resulted in the path for these women toward support being longer but in many cases being repeated unsuccessfully multiple times. This study concludes that thus all women face obstacles while seeking help in formal institutions, black women may face greater barriers in this path due to how structural racism is reproduced in the services that should guarantee rights.